COUNTER-HEGEMONY IN THE DEVELOPMENT OF BAWOMATALUO TOURIST DESTINATION, NIAS SELATAN, SUMATERA UTARA - Waruwu, Dermawan; Mudana, I Gede (E-Journal of Cultural Studies; Volume 11, Number 2, May 2018, 2018)
Bawomataluo which is located in South Nias, North Sumatra, has unique cultural and natural tourism. The area is referred to as “Bukit Matahari” (Hill of the Sun) as it is the area where tourists can enjoy the sunrise and sunset. However, the hegemonic practice performed by the government through its policies and the counter-hegemonic practice performed by the local people as the owner of the tourist destination have caused the area to be less developed. The problem of the study is how the counter-hegemonic practice is performed to develop the Bawomataluo tourist destination. This study is intended to understand and describe the form of the counter-hegemonic practice so it can widen the concepts of the related studies. The study used the qualitative method with the perspective of cultural studies. The theory of hegemony, the theory of power/knowledge, and the theory of social practice were used to analyze the data. The result of the study showed that the counter-hegemonic practice performed by the Bawomataluo people included the counter-hegemony towards the government’s policy, the counter-hegemony towards change and functional change of cultural heritage, and the counter-hegemony towards the tourism-related activities. They are all the accumulation of the local people’s disappointment with the government’s policy (hegemonic practice) which has been performed so far. As a result, the development of the tourist destination and infrastructure has not achieved the target yet. This present study offers a strategic political policy so the development of the tourist destination in Bawomataluo in particular and in Indonesia in general can be avoided from the hegemonic practice and counter-hegemonic practice. To this end, the tourist destination should be sustainably developed in order to improve the local people’s economy and increase the government’s income. The development should be the community-based one as well.